Nutrition Interventions Deliver Value in Healthcare: Real-World Evidence - Sulo S; Gramlich L; Benjamin J; McCauley S; Powers J; Sriram K; Mitchell K (Nutrition and Dietary Supplements, 2020)
Suela Sulo,1 Leah Gramlich,2 Jyoti Benjamin,3 Sharon McCauley,4 Jan Powers,5 Krishnan Sriram,6 Kristi Mitchell7 1Global Health Economics & Outcomes Research, Abbott, Chicago, IL, USA; 2Faculty of Medicine and Dentistry, University of Alberta, Edmonton, AB, Canada; 3Nutrition, Kaiser Permanente, Bellevue, WA, USA; 4Quality Management, Academy of Nutrition and Dietetics, Chicago, IL, USA; 5Nursing Research & Professional Practice, Parkview Health, Indianapolis, IN, USA; 6eICU, Advocate Health Care, Downers Grove, IL, USA; 7Health Policy, Avalere Health, Washington, DC, USACorrespondence: Suela SuloAbbott Nutrition, Abbott Park, Chicago, IL 60064, USATel +1 224-668-1377Fax +1 224-668-8355Email suela.sulo@abbott.comAbstract: Value is a key guiding principle in healthcare, yet value is defined in varying ways by different stakeholders. In this paper, we review evidence of the health and financial tolls of malnutrition or poor nutrition, report positive results from recent nutrition-focused quality improvement programs in hospitals, and discuss clinical and policy implications of realizing best-practice nutrition care. Hospitalized patients with malnutrition diagnoses have up to two-fold greater hospital costs for care compared to inpatient stays for adequately nourished patients. By contrast, implementation of nutrition care programs for hospitalized adults (nutrition status screening, assessment and diagnosis of malnutrition, oral nutritional supplements provided when indicated) is associated with substantial per-patient, per-episode healthcare savings approaching $4,000. Improved nutrition care has also been associated with fewer complications and faster recovery (shortened lengths of stay, lower readmission rates). Nutrition care thus delivers value, which is evidenced by better patient outcomes at cost savings to healthcare systems.Keywords: nutrition, value, healthcare, real-world evidence, quality improvement programs